2022
DOI: 10.1038/s41598-022-25177-3
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength effectiveness and optimal measurement timing for predicting functional outcomes of a geriatric hip fracture

Abstract: Handgrip strength (HGS) now draws attention as one of the predictors of outcomes following geriatric hip fracture; however, its effectiveness and the optimal time to assess HGS remain unknown. Herein, we aimed to determine the usefulness of HGS in predicting the outcomes of geriatric hip fracture and to find the most effective time to measure HGS in both the low muscle strength and normal hip fracture groups. The study was performed prospectively for 79 geriatric hip fracture patients. HGS was measured during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Han et al . found that pre‐ and post‐operative HGS was associated with walking ability and quality of life after hip fracture 20 . Selakovic et al .…”
Section: Discussionmentioning
confidence: 98%
“…Han et al . found that pre‐ and post‐operative HGS was associated with walking ability and quality of life after hip fracture 20 . Selakovic et al .…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, there were no significant differences in the intraoperative blood loss and surgical duration between the two groups, indicating that surgical timing would not affect the surgical course.The results are consistent with previous studies. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Handgrip strength (HGS) has been adopted as one of the diagnostic tools for sarcopenia and is gaining attention because of its relationship with osteoporotic hip fractures. Additionally, it has been highlighted as an easy and efficient modality for predicting the prognosis and degree of functional recovery after hip fractures [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Han et al reported that pre- and postoperative HGS reflected functional outcomes following hip fracture. They favored the postoperative HGS compared to preoperative HGS due to the higher prognostic value [ 5 ]. Although some authors have reported a relationship between lower HGS and hip fracture risk or lower functional recovery after surgery [ 6 , 8 , 9 ], there have also been contradicting results refuting the value of HGS in predicting hip fracture outcomes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%